Guatemala’s Water Supply, Sanitation, and Hygiene Poverty Diagnostic : Challenges and Opportunities - World Bank (Washington, DC: World Bank, 2018)
Poverty rates in Guatemala are among the highest in Latin America and the Caribbean, and Guatemala is now the second poorest country in the region, with only post-earthquake Haiti being poorer. Guatemala is an extreme outlier in the region in terms of chronic malnutrition, and almost half of all children in the country suffer from stunting. This report is part of a global initiative to improve the evidence base on the linkages between water supply, sanitation, and hygiene (WASH), human development, and poverty and seeks to understand this paradigm through a careful examination of trends in access to water and sanitation and in corresponding linkages to poverty and health. It also reviews the governance structure and expenditure plans underpinning service delivery in WASH sectors in Guatemala. Finally, the report the challenges facing the water and sanitation sector in Guatemala are significant and will require, among other things, stronger political leadership to successfully reform and regulate the sector, greater focus on rural sanitation, and increased spending and budget execution. One of the key elements of this diagnostics is highlight what conditions led to a struggling WASH sector, particularly in rural areas. Despite a steep increase in water and sanitation coverage in the last 15 years, sanitation coverage is falling far behind drinking water coverage, with the lowest levels of coverage in rural areas affecting predominantly indigenous populations.